'Princely Performed to the Honor of Our Nation': Leicester’s Men in the Netherlands as Agents of English Soft Power - Glider, Emily (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2025)
When Robert Dudley, earl of Leicester, travelled to the Netherlands leading Elizabeth I’s 1585 military intervention in the Dutch revolt, he brought along his acting troupe, which delivered entertainment during the welcome festivities, performing for several of Dudley’s major diplomatic interlocutors. While scholars have long recognized the significance of this tour for English theatre history, the international relations context that brought the actors to Europe has received little attention. Drawing on recent historical research exploring ‘cultural diplomacy’ in the early modern world, I reevaluate Leicester’s Men as agents of English ‘soft power’ who built international influence through pageantry, drama, and ritual gift-giving at a strategically significant diplomatic occasion.